Character Education as A Form of Strengthening School Cultural in SDIT Imam Syafi’i Kebumen - M Slamet Yahya (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
This article is intended to describe the implementation of character education in order to strengthen the school culture at SDIT Imam Syafi'i Kebumen. Field data is collected through interviews, observations and then analyzed in qualitative. The findings are (a) character education at SDIT Imam Syafi'i in the conversation of the meaning of tarbiyah, ta'dib and ta'lim consisting of responsibility, discipline and religious characters; (b) the most prominent character in SDIT Imam Syafi'I is simplicity with a simple method that is exemplary; and (c) forms of educational activities as a strengthening of school culture, namely routine, spontaneous and conditioning activities.